Kajian Teori Empiris Manajemen Waktu pada Pelaksanaan Proyek Pembangunan Unit Rumah Tinggal di Waikabubak, Sumba Barat, Nusa Tenggara Timur dengan PERMEN PU PR 2016 - Tala Pessy , Simon Stenly ; Suhudi ; Wijaya, Handika Setya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Provide legal certainty, protecting the dam trial, provide a sense of fairness, as well as creating order is the purpose and benefits of the existence of the Act. Similarly, in the world of construction projects. In the world of construction known regulation of theMinister of public works Housing Legislation in Indonesia was established by the President to the Minister related to the running of the Statute accordingly. MINISTERIAL REGULATION PU PR No. 5/2016 About Permit Building parts of the one-storey building classification and MINISTERIAL REGULATION No. 28/ 2016 PUPR of unit price analysis of the field of public works part 4 field of copyright works is the rule be a reference to analyze the writing of the thesis. The object of the research was the execution of the construction of the housing units lived in Waikabubak, West Sumba. Quality, cost, time is a very important point in the world of construction. Comparative analysis of management time into material for comparative studies i.e. Time planning with an implementation time in customize according to MINISTERIAL REGULATION PU PR.